Human Capital Development and Unemployment in Uganda: The Keynesian Theory of Unemployment in Perspective - Kijjambu, Fredrick Nsambu; Musiita, Benjamin; Katarangi, Asaph Kaburura (Journal of Economics and Behavioral Studies, 2024)
This study delves into the dynamic relationship between human capital development and unemployment in Uganda, employing a Vector Error Correction Model (VECM) to analyze time series data on education and health expenditures as a percentage of GDP, Gross Fixed Capital Formation, and Government Consumption Expenditure. The study applied aggregated secondary data on an annual basis trenching from 1986 to 2022 and from the World Bank Development Indicators (WBDI). For data analysis purposes, the STATA software was utilized. The findings reveal a significant negative effect of education expenditure on unemployment rates in the short term, highlighting the critical role of educational investment in mitigating unemployment. Health expenditure is similarly beneficial in the long term, though its short-term effects are less pronounced. The results advocate for prioritizing educational spending in economic policies to foster sustainable employment growth. These insights are crucial for policymakers aiming to leverage human capital development as a means to counter unemployment and promote economic stability.